Embodied energy optimization for alternate design and construction techniques for reinforcement concrete slab - Jasim Nadhem Naim (School of Environmental Engineering, University Malaysia Perlis, 2016)
The construction projects require costly investments of time and money. One 0f the primary concern is the environmental costs of construction such as the carbon dioxide and other greenhouse gases emitted into the atmosphere that are came as a result of construction activities. Therefore, engineers exercise their abilities early on in the design phase of construction projects to help reduce the cost and carbon footprint by lessening the amount of materials required. One of the important aim of design is increasing the sustainability of the buildings in terms of considering the embodied energy. This research will focus on Comparison between different concrete slab systems with alternate design and different construction techniques. Types of slab systems will be use are hollow-core units (precast), reinforced concrete solid slab, hollow core, ribbed slab and post-tensioning flat slab. Analysis of multi store buildings slab systems. Detailing of manual calculation on the slabs systems, identification of environmental impact and calculating the embodied energy. Using "cradle to site" methods to find the embodied energy. The embodied energy data was obtained through analysis of the data on the quantity of the material used to build the structure provided. This project was constructed using the 4 types of the slab system that already mentioned. The bill of quantity required for each slab system was identified then by using the material coefficients the total Embodied Energy for each slab system were calculated. New methodology need suggested In order to optimise the total Embodied Energy of the structural design of a building slab system